Course H[OER]oes? Ethical Data Collection in Open Digital Societies - Essmiller, Kathy; Colquhoun, Cristina; Reiter, Holly (Proceedings of the International Conference on Networked Learning, 2024)
In 2021 networked learning community scholars responded to a call inviting discussion of how they made meaning of the term networked learning and understood its associated practices (Gourlay et al., 2021). The insights shared and questions raised have implications for all educators and scholars working with and among students of all levels. The purpose of this roundtable discussion will be to consider the relevance of these insights and questions for those whose work centers open educational resources and collection of data related to their use. In particular, participants will discuss whether and how to gather, analyse and store data in ways which honour the "trusting relationships" (Gourlay et al., 2021, p. 337) considered essential to "socially just" (Bali, 2020, n.p.) networked learning experiences. Discussants will be invited to unravel to what extent the use, modification, or creation of open educational resources qualify as networked learning, explore the impact the use of related technology has on pedagogy, and work together to explicate whom, in fact, such practices and connections are ultimately for (Gourlay et al., 2021). The authors of this paper will share research and experiences related to the development of a student data privacy framework intended to guide data collection practices for materials created in association with the academic library's open educational resource publishing program.